Fortification of extruded snacks with chitosan: Effects on techno functional and sensory quality. (15th August 2018) - Kumar, Raushan; Xavier, K.A. Martin; Lekshmi, Manjusha; Balange, Amjad; Gudipati, Venkateshwarlu
Highlights: Functional extruded snack was prepared with different levels of chitosan. Effects of physical, chemical and functional qualities were evaluated. Increased level of chitosan in functional snacks reduced oxidation. Crystallinity index was higher in snacks with higher chitosan level. Abstract: Chitosan is a dietary fibre that possesses numerous functional, technological and physiological properties useful in improving food quality. Owing to its fat absorbing ability, chitosan is widely consumed as a health supplement in the form of tablets and capsules. With a view to enhance it consumption and availability, the current work was taken up to evaluate techno-functional quality improvement of shrimp based extruded snacks fortified with chitosan. Chitosan powder at 1, 2 and 3% (w/w) level was added to the base material (corn flour and rice flour in the ratio of 70:30 and 15% Acetes powder) for extrusion. Addition of chitosan in acetes based snacks significantly reduced expansion ratio, porosity and crispiness and increased the hardness value of the product. Chitosan addition had a significant effect ( p > 0.05) on the moisture retention and total protein contents of the products as well. Thiobarbituric acid reactive substances (TBARS) value of chitosan fortified extrudate showed a significantly lower value than the control sample. A higher level of chitosan also resulted in colour reduction of the final product. The FTIR spectra of extrudate confirmed the stability of chitosan during extrusion conditions. The sensory score revealed that extrudate fortified with 1% chitosan was comparable to control sample. From this study it is concluded that 1% chitosan can be incorporated in Acetes based extruded snacks for an increased level of functionality.